Application of L-Shaped Zigzag Steel Fibers with Different Parameters in Asphalt Mixtures - Qingguo Yang; Wujing Yin; Jiawei Cheng; Ya Li; Yu Zhou; Kelin Chen; Yunhao Li (Fibers, 2025)
Taking AC-13 asphalt mixture as the matrix, this research delves into the impacts of assorted steel fibers on AC-13 asphalt mixture, especially the influence of 17.5 mm × 17.5 mm L-shaped steel fibers. A gradient design with mass dosages of 0%, 1%, 2%, and 3% was employed to evaluate the reinforcement effect of L-shaped steel fiber-reinforced asphalt mixture compared with conventional mixture. Also, comparative analysis between L-shaped and straight steel fibers was conducted through comprehensive mechanical performance tests, including the Marshall stability test, high-temperature wheel tracking test, low-temperature beam bending test, freeze–thaw splitting strength test, and immersion Marshall test. The results demonstrate that L-shaped steel fibers significantly improve the comprehensive mechanical properties of asphalt mixture compared to conventional asphalt mixture, showing remarkable improvements in high-temperature stability, low-temperature crack resistance, and water stability. The overall performance enhancement effect increases by approximately 20%. Compared with straight steel fibers, the performance improvement of the mixtures is slightly greater, with the optimal performance achieved at 2% mass dosage. The standard deviation and coefficient of variation are used to reflect the degree of data dispersion. The results show that the data of L-shaped steel fibers have relatively smaller fluctuations, being more uniform and stable.